Economics of physical activity in low-income and middle- income countries: a systematic review. Issue 1 (15th January 2021) - Ranasinghe, Priyanga Diloshini; Pokhrel, Subhash; Anokye, Nana Kwame
Abstract : Background: Promotion of physical activity (PA) among populations is a global health investment. However, evidence on economic aspects of PA is sparse and scattered in low-income and middle-income countries (LMICs). Objective: The objective of this study was to summarise the available evidence on economics of PA in LMICs, identify potential target variables for policy and report gaps in the existing economic evidence alongside research recommendations. Data sources: A systematic review of the electronic databases (Scopus, Web of Science and SPORTDiscus) and grey literature. Study eligibility criteria: Cost-of-illness studies, economic evaluations, interventions and descriptive studies on economic factors associated with PA using preset eligibility criteria. Study appraisal and synthesis of methods: Screening, study selection and quality appraisal based on standard checklists performed by two reviewers with consensus of a third reviewer. Descriptive synthesis of data was performed. Results: The majority of the studies were from upper-middle-income countries (n=16, 88.8%) and mainly from Brazil (n=9, 50%). Only one economic evaluation study was found. The focus of the reviewed literature spanned the economic burden of physical inactivity (n=4, 22%), relationship between PA and costs (n=6, 46%) and socioeconomic determinants of PA (n=7, 39%). The findings showed a considerable economic burden due to insufficient PA, with LMICs accounting for 75% of disability-adjusted life years (DALYs) globally due to insufficient PA. Socioeconomic correlates of PA were identified, and inverse relationship of PA with the cost of chronic diseases was established. Regular PA along with drug treatment as a treatment scheme for chronic diseases showed advantages with a cost–utility ratio of US3.21/quality-adjusted life year (QALY) compared with the drug treatment-only group (US3.92/QALY) by the only economic evaluation conducted in the LMIC, Brazil. Limitations: Meta-analysis was not performed due to heterogeneity of the studies. Conclusions and recommendations: Economic evaluation studies for PA promotion interventions/strategies and local research from low-income countries are grossly inadequate. Setting economic research agenda in LMICs ought to be prioritised in those areas. PROSPERO registration number: CRD42018099856.